ANALISIS PERBAIKAN DESAIN KEMASAN PRODUK UNTUK MENINGKATKAN EFISIENSI PENYIMPANAN DAN DISTRIBUSI - Gyas Khairan; Fadlan Tajudin Ramadhan; Naela Soraya; Lisana Tartila (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study examines packaging design improvements to enhance storage and distribution efficiency in supply chains, with a focus on Indonesia as a developing country. Using a Systematic Literature Review (SLR) of 10 international journals (2020–2025), the research identifies key strategies such as volumetric analysis, stacked pallet load units (SPLUs), interlock stacking, and lean warehousing. Findings indicate that space utilization can be increased by up to 67%, with cost reductions of 15–25%. However, implementation faces challenges due to Indonesia’s high humidity, limited recycling infrastructure, and lack of packaging standardization. The study concludes that a phased approach—prioritizing operational efficiency before integrating environmental sustainability—is most feasible for the Indonesian context. Practical recommendations are provided for industry, policymakers, and future research.Keywords: packaging design optimization, storage efficiency, sustainable logistics, supply chain management, Indonesia logistics